PROTECTING MINORS IN RELATION TO INTERACTIVE SOFTWARE - López Jiménez, David; Dittmar, Eduardo Carlos; Vargas Portillo, Jenny Patricia (Law, State and Telecommunications Review, 2021)
Purpose - The objective of this work is to analyze minors’ participation with interactive software. Methodology/approach/design - The Spanish regulations in effect on this matter will be analyzed. Similarly, applicable best practice instruments that have been adopted will be analyzed. Findings - The interactive software industry’s self-regulation could be a thought-provoking tool to complement legal regulations to protect minors. Practical implications - The repercussions of this research analysis can be useful for the interactive software industry, civil society, and the public sector. Originality/value - This research article shows the risks that minors face in the digital world. The study provides a perspective that highlights the harmful and illegal content that affects minors.